Aggressive dentigerous cyst in the maxillary sinus, originating from an ectopically erupted maxillary third molar: a case report. Issue 3 (October 2015) - Joseph, Benny; Vyloppilli, Suresh; Kumar K.P., Manoj; Anirudhan, Anroop; Kumar, Nithin; Sayd, Shermil
Abstract : A dentigerous cyst (DC) arises from the reduced enamel epithelium and may extend into the surrounding bone, growing un-noticed to such extensive sizes as to occupy a considerable portion of the maxillary sinus. An ectopically erupted tooth associated with a DC in the maxillary sinus presents itself as a confounding problem, which may lead to maxillary sinusitis. A case of such a DC associated with an ectopic maxillary third molar tooth in the left maxillary sinus cavity is presented, which is of interest because of its less commonly occurring site and the age of the patient, who is only 15 years of age. Advanced imaging methods such as computed tomography were carried out to determine its extent and the cyst was enucleated in toto .